Seaweed bioprospecting in the Mediterranean Sea and the potential exploitation - Loredana Stabili; Maria Immacolata Acquaviva; Ester Cecere; Carmela Gerardi; Antonella Petrocelli; Elisa Quarta (Food Chemistry Advances)
Algae attract interest as a source of bioactive compounds with diverse properties. In this study, we conducted a comparative analysis of the potential of nine seaweeds collected in the Mediterranean Sea investigating their antibacterial, antioxidant, and nutritional properties. The species analyzed were: Chaetomorpha linum, Rama rupestris, Gracilaria dura, Gracilaria gracilis, Gracilariopsis longissima, Grateloupia turuturu, Hypnea corona, Gongolaria barbata and Undaria pinnatifida. All lipidic extracts exhibited antibacterial activity against different Vibrio species. Lipidic extracts from H. corona, G. barbata, R. rupestris and U. pinnatifida inhibited some antibiotic-resistant human pathogens. Palmitic and linoleic acids appear to be involved in these activities. The extracts also showed antioxidant activity with the highest value recorded for G. barbata (1009.560±115.174 mmol Trolox equivalent/g extract). Gas chromatography revealed the presence of free saturated (SAFAs), monounsaturated (MUFAs), polyunsaturated (PUFAs) fatty acids with SAFAs prevailing in G. longissima (67.30±13.10%) and PUFAs in C. linum (71.97±13.48%). The seaweeds showed a noteworthy ω6/ω3 ratio. The results are discussed in the light of the biotechnological applications indicating that C. linum, G. turuturu and U. pinnatifida have the highest quality fatty acid profiles useful in nutraceuticals. Hypnea corona, G. barbata, R. rupestris and U. pinnatifida are more promising for pharmaceutical use.